2011
DOI: 10.1109/lpt.2011.2147298
|View full text |Cite
|
Sign up to set email alerts
|

Mode Selectivity in Bragg Reflection Waveguide Lasers

Abstract: Bragg reflection waveguides (BRWs) have recently been proposed for the development of high performance single mode lasers and nonlinear frequency conversion devices. In this letter, we experimentally demonstrate single transverse photonic bandgap mode operation in a large core BRW laser with low threshold current density A cm and high characteristic temperature K . The mode selectivity is examined theoretically using the effective index method and experimentally via far field and gain spectra measurements. Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The calculation is conducted separately below 330 mA and beyond 380 mA, because the wavelength suddenly red shifts around 330 mA, due to the special BRW mode temperature change. [21] The pump wavelength shift with current is about 2.73 × 10 −3 nm/mA below 330 mA and about 1.69×10 −3 nm/mA beyond 380 mA. The tuning curve of parametric wavelength is shown in Fig.…”
mentioning
confidence: 89%
“…The calculation is conducted separately below 330 mA and beyond 380 mA, because the wavelength suddenly red shifts around 330 mA, due to the special BRW mode temperature change. [21] The pump wavelength shift with current is about 2.73 × 10 −3 nm/mA below 330 mA and about 1.69×10 −3 nm/mA beyond 380 mA. The tuning curve of parametric wavelength is shown in Fig.…”
mentioning
confidence: 89%
“…Losses are more significant in Bragg modes (pump), where leakage losses can vary widely [between 5 and 50 dB ∕ cm depending on many parameters including the Bragg stack confinement and the value of the etch depth D in a two-dimensional (2D) ridge]. Scattering losses, however, vary less than their leakage counterparts and are found to range between 2 and 10 dB ∕ cm [27]. If the lower values of these ranges are to be used as a guide, the pump mode losses will only result in a reduction of the pair generation efficiency by 30-50% in a 2 mm-long waveguide.…”
Section: Properties Of Generated Biphotonsmentioning
confidence: 99%
“…Two-dimensional photonic crystal surface-emitting lasers have previously been reported that are capable of producing a range of beam patterns [11]. In recent years, edge-emitting diode lasers based on double-sided quarterwave Bragg reflection waveguides (QtW-BRWs) or so-called one-dimensional photonic crystals have been developed, whose vertical FF distribution shows two main lobes with many side peaks [12][13][14]. However, for QtW-BRWs in which the layers of the Bragg reflectors have a thickness equal to one-quarter of the transverse vector component of the guided mode, the PBG mode is placed in the center of the stop band, which results in maximum confinement of the optical field in the core defect layer.…”
Section: Introductionmentioning
confidence: 99%